Casino security and gaming resort investigations - Boss, Derk J.; Zajic, Alan W. (New York : Routledge, 2019)
Casino and Gaming Resort Investigations addresses the continued and growing need for gaming security professionals to properly and successfully investigate the increasing and unique types of crime they will face in their careers. As the gaming industry has grown, so has the need for competent and highly skilled investigators who must be prepared to manage a case of employee theft one day to a sophisticated sports book scam the next. This book provides the reader with the fundamental knowledge needed to understand how each gaming and non-gaming department functions and interacts within the overall gaming resort, allowing the investigator to determine and focus on the important elements of any investigation in any area. Each chapter delivers a background of a department or type of crime normally seen in the gaming environment, and then discusses what should be considered important or even critical for the investigator to know or determine in the course of the investigation. Likely scenarios, case histories, and tips, as well as cautions for investigators to be aware of, are used throughout the book. This book was written for and directed at gaming security and surveillance professionals, including gaming regulators, and tribal gaming authorities, who are almost daily confronted by the ingenious and the most common scams, theft, and frauds that are perpetrated in the gaming world.
The art of investigations -- 2.field investigations -- Marketing considerations and investigations -- Objective and impartial investigations -- Understanding the scope of the investigation -- Starting the investigation -- Written reports -- Interviews -- Ethics in investigations -- Prosecution -- Jurisdictions, regulations and gaming environments -- Investigations and liability -- Non-gaming investigations -- Hotel investigations -- Food and beverage investigations -- Claim investigations -- Vehicle accidents and auto theft -- Post investigation best practices -- Gaming investigations -- Investigative concepts -- Covert surveillance investigations -- Employee theft and fraud -- Outside agents and collusion -- Gaming investigations -- Cage -- Slots -- Table games -- Player's club -- Marketing scams -- Keno and bingo -- Race and sports book -- Night clubs and party pools -- Glossary -- Index -- Appendix.
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Casinos -- Security measures -- Handbooks, manuals, etc; Electronic surveillance -- Handbooks, manuals, etc; Gambling -- Corrupt practices; Criminal investigation; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism; COMPUTERS / Security / General; LAW / Forensic Science